FAKTOR –FAKTOR YANG MEMPENGARUHI KEPATUHAN PAJAK WAJIB PAJAK ORANG PRIBADI DALAM RANGKA PENERAPAN SISTEM SELF ASESSMENT - Fibria Anggraini (Balance Vocation Accounting Journal, 2017)
The purpose of this study was to analyze the factors that affect tax compliance (tax compliance) individual taxpayers This study uses the variable individual behavior, motivation and tax knowledge as the independent variable and tax compliance individual taxpayers as the dependent variable. Data analysis was performed using multiple linear regression analysis with SPSS for Windows Version 19.00. The results of this study indicate that individual behavior, motivation and tax knowledge have significant effect on tax compliance individual taxpayers . Keywords: individual behavior, motivation, tax knowledge, tax compliance.